2017
DOI: 10.4172/2169-0316.1000221
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on the Dependency of Bursting Strength of Knitted Fabrics on Knit Structures

Abstract: Knitted fabrics bursting strength dependency was investigated. The investigation was by reviewing previously done and published research articles. In this investigation the dependency of bursting strengths on knit structures was identified and analyzed. Different findings of different scholars on bursting strengths of different knitted fabrics have been discussed in this review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…The bursting strength of sonicated samples was determined to be 213 kPa at 70°C, 221 kPa at 65°C, 237 kPa at 60°C, and 235 kPa at 55°C, respectively. The bursting strength of the pretreated fabric increased to the same extent as the temperature decreased, as expected by the literature (Sitotaw 2017). Aside from that, the fabric strength values in samples formed by the rst and second reuse of bath chemicals are higher than in other samples.…”
Section: Effects On Fabric Strengthsupporting
confidence: 87%
“…The bursting strength of sonicated samples was determined to be 213 kPa at 70°C, 221 kPa at 65°C, 237 kPa at 60°C, and 235 kPa at 55°C, respectively. The bursting strength of the pretreated fabric increased to the same extent as the temperature decreased, as expected by the literature (Sitotaw 2017). Aside from that, the fabric strength values in samples formed by the rst and second reuse of bath chemicals are higher than in other samples.…”
Section: Effects On Fabric Strengthsupporting
confidence: 87%
“…It is a function of fiber quality (measured as deniers), knitting patterns and types of polymers used [179]. One review on this subject concluded that bursting strength of knitted fabrics depend not only on fabric structures and fiber types, but also the yarns used [180].…”
Section: Importance Of Durability and Functional Survival Of Nets In mentioning
confidence: 99%
“…Although the diameters are the same, this is an expected result due to the air channel inside the hollow fiber. The bursting strength is the force that must be exerted perpendicular to the fabric surface to break off the fabric [16]. The value helps to determine the quality of the fabric and how safe it is for different applications.…”
Section: Resultsmentioning
confidence: 99%